Farm friends : the vet visit - Derting, Kimberly; Johannes, Shelli R.; Humphrey, Kristen (2024)
"When a new foal is born at Poppy's family farm, the local veterinarian comes to make sure it, and all the other baby animals, are healthy"--Title verso page.
Ages 5-8.
Grades 2-3.
530L
Keywords: Animals -- Infancy -- Juvenile fiction; Veterinarians -- Juvenile fiction; Farm life -- Juvenile fiction; Animals -- Infancy -- Fiction; Veterinarians -- Fiction; Farm life -- Fiction